2020
DOI: 10.3389/fnut.2020.550287
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Aspects of Subjective Sleep Quality of Healthy Volunteers by Ingestion of Porcine Placental Extract: A Randomized Cross-Over Pilot Study

Abstract: Objectives: This study assessed the effects of oral porcine placental extract (PPE) on sleep quality of healthy volunteers not satisfied with their sleep.Design: This study used a randomized, placebo-controlled, double-blind, cross-over clinical pilot study.Setting: This study was conducted under an outpatient multicenter setting in Japan.Interventions: A total of 20 healthy Japanese volunteers aged between 28 and 73, whose Pittsburgh Sleep Quality Index global scores were between 6 and 10, successfully comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, it is unclear whether improved sleep quality was an effect of eqPE in this case. In human studies, it has been reported that porcine placental extract does not affect the duration of sleep, but it improves the quality of sleep (Nagase et al., 2020); therefore, it is assumed that eqPE had a similar effect in dogs. Currently, we are conducting research using mouse models with sleep disorders to elucidate the effects and mechanism of eqPE.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether improved sleep quality was an effect of eqPE in this case. In human studies, it has been reported that porcine placental extract does not affect the duration of sleep, but it improves the quality of sleep (Nagase et al., 2020); therefore, it is assumed that eqPE had a similar effect in dogs. Currently, we are conducting research using mouse models with sleep disorders to elucidate the effects and mechanism of eqPE.…”
Section: Discussionmentioning
confidence: 99%
“…Several old documents describing the usage of the placenta as traditional medicines have been discovered in Asian countries; for example, a Chinese historical book, "Compendium of Materia Medica (Ben Cao Gang Mu)" mentioned the use of dried human placenta (Ze He Che) as a revitalizer [4]. Recently, placental extracts produced by digesting the placenta of several animals with proteases or acids have been used for both inner and outer beauty, especially in Asian countries, including Japan [5][6][7][8][9]. For application in cosmetics, although traditional placental extracts produced solely by proteolysis have been reported to have the property to stimulate the proliferation of dermal fibroblasts [10][11][12], their moisturizing effects were not sufficient, and they could not stimulate the proliferation of epidermal keratinocytes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Doctors chose direct application of HPE as their priority for burned patients to both prevent infection and promote healing [ 14 ]. The placental extract is useful for the maintenance of human skin quality [ 15 ], improvement of sleep quality [ 16 ], reduction of menopausal symptoms [ 17 ], and maintenance of joint functions in knee osteoarthritis patients [ 18 ]. Multiple studies have demonstrated that HPE is also involved in immune regulation.…”
Section: Introductionmentioning
confidence: 99%